2021
DOI: 10.1097/md.0000000000026645
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fetal cardiac diastolic function of gestational diabetes mellitus using dual-gate Doppler

Abstract: Gestational Diabetes Mellitus (GDM), as a common complication of pregnancy, has an increasing trend globally. GDM leads to maternal complications and fetal complications. Fetal cardiac diastolic dysfunction is strongly associated with GDM. This study aims to assess the ventricular diastolic function of fetuses exposed to GDM by looking into the diagnostic parameters using both conventional method and Dual-gate Doppler method (DD). And to investigate the potential of DD method in early detection of fetal cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…A previous study suggested that fetuses of diabetic mothers may encounter an increased myocardial velocity in the atrioventricular annuluses. This aids in balancing the restricted ventricular compliance during early diastole 26 . This acceleration is especially noticeable in the right ventricle, and diastolic functions are more susceptible to being damaged due to elevated blood glucose levels that cause placental vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that fetuses of diabetic mothers may encounter an increased myocardial velocity in the atrioventricular annuluses. This aids in balancing the restricted ventricular compliance during early diastole 26 . This acceleration is especially noticeable in the right ventricle, and diastolic functions are more susceptible to being damaged due to elevated blood glucose levels that cause placental vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This aids in balancing the restricted ventricular compliance during early diastole. 26 This acceleration is especially noticeable in the right ventricle, and diastolic functions are more susceptible to being damaged due to elevated blood glucose levels that cause placental vascular resistance.…”
Section: F I G U R Ementioning
confidence: 99%
“…17 These subtle subclinical changes likely precede diastolic dysfunction, as demonstrated using conventional ultrasound parameters during the third trimester. 18 A similar impairment of diastolic function was also observed in the fetuses of mothers with gestational diabetes 19 ; thus, hyperglycemia-induced cardiac remodeling and the consequent fetal adaptation may be responsible for this phenomenon. Indeed, we observed a positive correlation between the percentage of time spent in hyperglycemia, A1c, and diastolic function, mainly regarding the RV A wave.…”
Section: Discussionmentioning
confidence: 81%
“…One study found that tricuspid E' values and E'/A' ratio were lower in the diabetic group compared to the control group, but no significant difference was found between the pre-GDM and GDM groups. 31 Hou et al 32 did not detect a significant difference in tricuspid E' and E'/A' ratio in GDM patients. In our study, there were no significant changes in tricuspid E', A' values, and E'/A' ratio in the MHD group, implying that heart disease does not cause changes in fetal RV diastolic function.…”
Section: Discussionmentioning
confidence: 87%